Tingkat Kepuasan Pasien terhadap Pelayanan Kefarmasian di Puskesmas Pahandut Kota Palangka Raya: Level of Patient Satisfaction on Pharmaceutical Services in Community Health Centers of Pahandut Palangka Raya - Nurul Chusna; Titra Fetriana; Rabiatul Adawiyah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to determine the level of patient satisfaction with pharmaceutical services at the Pahandut Palangka Raya Community Health Center. This research method is descriptive. The sample in this study were 94 respondents, namely outpatients who received pharmacy services at the Pahandut Palangka Raya Community Health Center. The sampling technique in this study used a purposive sampling technique. The results of the study of patient satisfaction with pharmaceutical services based on the type of service obtained a score of 208 data located in the